The development of scientific activity in Russian universities - Marina Vasiljeva; Vadim V. Ponkratov; Tatyana Volkova; Saida Khairova; Natalya Nikitina; Olesya Dudnik; Maria Alimova; N. V. Kuznetsov; Izabella Damdinovna Ėljakova (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The aim of this article was to develop scientific activity in Russian universities. Using the survey method, a sample of quantitative indicators of research output for the years 2011-2019 was formed. The respondents were comprised of 934 lecturers from 13 universities in Russia with different work experience, academic degrees, and indicators of scientific activity. The main components method was used to study the structure of scientific activity productivity indicators. Using the method of additive convolution, a five-factor integral model of the structure of scientific activity of a teacher was formed to evaluate the individual and collective productivity of scientific activity. The factor values and the integral indicator of scientific activity output were calculated, showing that the individual growth rates of the young lecturers' output exceeded the growth rates of the older lecturers. Destructive factors relating to the scientific activity output of the lecturers and researchers in Russian universities (divided into two groups of young scientists and senior scientists) were determined and systematized based on the level of dominant influence. The features of the influence of the factor of emotional burnout on the scientific productivity of university teachers were revealed.
Keywords: 650; higher education; publication productivity; researcher; Russia; university; scientific performance